Prevalence of helicobacter pylori infection and its histopathological correlation in adult celiac patients - Oral, Ali Cagri; Yalniz, Mehmet; Kirsoy, Furkan; Ozercan, Abdullah Mubin; Cicek, Sedat; Bahcecioglu, Ibrahim Halil (Bayrakol Medical Publisher, 2025)
Aim: Celiac disease (CD) is a chronic autoimmune enteropathy associated with gluten intake in genetically predisposed individuals. Helicobacter pylori (H. pylori) is a common gastric pathogen, and its relationship with CD remains unclear. This study aimed to investigate the prevalence of H. pylori infection and its histopathological effects in adult CD patients. Material and Methods: This retrospective study includes patients diagnosed with CH at the Gastroenterology Clinic of F & imath;rat University Hospital. Patients with a confirmed diagnosis of CH based on duodenal biopsy were included in the study. H. pylori status was determined by histological evaluation of gastric biopsies taken according to the Sidney protocol. Demographic, clinical, and histopathological data were obtained from patient files. Results: A total of 216 CH patients were included in the study (174 [80.6%] H. pylori positive, 42 [19.4%] H. pylori negative). There were no significant differences in gender distribution and Marsh classification between the groups (p>0.05). Marsh 3A and 3B (31.6%) were the most common in H. pylori-positive cases, while Marsh 3B (38.1%) was the most common in H. pylori-negative cases. Chronic gastritis was observed at a high rate in both groups (positive 96%; negative 95.2%). Discussion: Although H. pylori infection is common in patients with Crohn's disease, no significant effect on histopathological findings and Marsh stages has been detected. Our findings indicate that the effect of H. pylori on Crohn's disease remains controversial and therefore requires large-scale, multicenter prospective studies.
Keywords: celiac disease; helicobacter pylori; marsh classification; histopathology